Determinants and geographic distribution of unimproved sanitation facilities in sub-Saharan Africa, spatial and multilevel analysis using demographic and health survey (DHS) data - Lidetu Demoze; Mitkie Tigabie; Eshetu Abera Worede; Helen Brhan; Zemichael Gizaw; Amensisa Hailu Tesfaye; Gelila Yitageasu (BMC Public Health)
Abstract Background One-third of the population in sub-Saharan Africa does not have access to adequate hygiene and sanitation facilities. Many still lack decent and functional toilets, impacting health, dignity, and development. Therefore, this study aimed to assess the geographical distribution and factors associated with unimproved sanitation facilities in sub-Saharan Africa. Methods This study used Demographic and Health Survey (DHS) data from 500,845 households within 20,492 clusters across 34 sub-Saharan African countries, which were weighted, cleaned, and analysed using STATA version 17. Spatial analyses were conducted using ArcGIS software version 10.7 and Kulldorff’s SaTScan software version 10.1. Multilevel analysis was employed to identify contributing factors, with associations presented as adjusted odds ratios and 95% confidence intervals (p < 0.05). Results Significant spatial clustering and hotspots of unimproved sanitation facilities were identified within sub-Saharan Africa. The magnitude of unimproved sanitation facilities in sub-Saharan Africa was 48.88% (95% CI: 48.74–49.02%). The magnitude of unimproved sanitation was lowest in Malawi at 16.70% and highest in Chad at 88.52%. Several individual and community level factors were significantly associated with the utilization of unimproved sanitation facilities. At the individual level, female-headed households and those with access to improved drinking water source were less likely to use unimproved sanitation. In contrast, households headed by individuals aged 11–35 and 36–50 years, divorced households, and households with more than four members were associated with greater use of unimproved sanitation facilities. Additionally, households in the poorest, poorer, middle, and richer wealth categories were also associated with a greater use of unimproved sanitation facilities. Furthermore, households with water sources located in the yard/plot and off-premises had higher odds of using unimproved sanitation. At the community level, rural residence and lack of media exposure were associated with greater use of unimproved sanitation facilities. Conclusion Unimproved sanitation facilities remain a major public health challenge in sub-Saharan Africa, with significant regional disparities and a 48% magnitude. Addressing this issue requires targeted government policies, financial support for sanitation infrastructure, improved water supply, hygiene awareness campaigns, increased media exposure, and better sanitation facilities in rural areas.